Settlement Of Defaults In Restructuring Efforts In Credit Agreements At Bank Pasar Rembang (Case Study Decision Number: 7/Pdt.G/2021/Pn.Rbg) - Riza Zulfikar; Novi Prisela Putri; Hadi Purnomo (Jurnal Restorasi : Hukum dan Politik, 2023)
Engagements or agreements through credit transactions carried out by banks are bound by a credit agreement, so that a legal relationship arises between the binding parties. Because there is an imbalance between creditors and debtors, the weaker party is unable to fulfil the agreement, and ends up causing problems between the two parties. For this reason, credit restructuring is carried out to resolve problem loans. However, in this case, not only debtors can default, but also creditors, who violate the restructuring agreement. Which led to the issuance of the Rembang District Court decision Number 7/PDT.G/2021/PN Rbg. Through the trial of the debtor's lawsuit whose restructuring agreement was rejected by the creditor. The method used in this case study is juridical research where this research examines the applicable legal provisions. The data source used is secondary data, both secondary and tertiary legal materials using library data collection techniques, namely document study by collecting and studying legal books, literature, laws and regulations related to the object of research and other reading related to writing. This case study and the documents examined are court decisions. Data analysis uses qualitative juridical methods. The results of this research can be concluded that in the case study of this research, bank credit restructuring is a step taken by the debtor because he is still cooperative, always maintains a relationship with the bank, and has good faith and has the opportunity to fulfil his obligations, but the bank as a creditor commits an act of default. by denying the restructuring efforts proposed by the debtor which had also been agreed upon by the creditor by referring to Bank Indonesia Regulation number 14/15/PBI/2012 and the bank's internal procedures, in the process of which the creditor conducted an auction of the collateral objects listed in the credit agreement clause without notification and agreement with the debtor. This problem resulted in a lawsuit filed by the debtor with the Rembang District Court. The judge's consideration in the decision in this case was that the judge stated that the debtor's credit restructuring was cancelled. The refusal (drop) is the correct action based on the verstek decision. However, the judge must also consider first looking at the Derivative of the credit agreement, namely credit restructuring.